ALDH1 Bio-activates Nifuroxazide to Eradicate ALDHHigh Melanoma-Initiating Cells. Issue 12 (20th December 2018) - Sarvi, Sana; Crispin, Richard; Lu, Yuting; Zeng, Lifan; Hurley, Thomas D.; Houston, Douglas R.; von Kriegsheim, Alex; Chen, Che-Hong; Mochly-Rosen, Daria; Ranzani, Marco; Mathers, Marie E.; Xu, Xiaowei; et al.
Summary: 5-Nitrofurans are antibiotic pro-drugs that have potential as cancer therapeutics. Here, we show that 5-nitrofurans can be bio-activated by aldehyde dehydrogenase (ALDH) 1A1/1A3 enzymes that are highly expressed in a subpopulation of cancer-initiating (stem) cells. We discover that the 5-nitrofuran, nifuroxazide, is selective for bio-activation by ALDH1 isoforms over ALDH2, whereby it both oxidizes ALDH1 and is converted to cytotoxic metabolites in a two-hit pro-drug mechanism. We show that ALDH1 High melanoma cells are sensitive to nifuroxazide, while ALDH1A3 loss-of-function mutations confer drug resistance. In tumors, nifuroxazide targets ALDH1 High melanoma subpopulations with the subsequent loss of melanoma-initiating cell potential. BRAF and MEK inhibitor therapy increases ALDH1 expression in patient melanomas, and effectively combines with nifuroxazide in melanoma cell models. The selective eradication of ALDH1 High cells by nifuroxazide-ALDH1 activation goes beyond current strategies based on inhibiting ALDH1 and provides a rational basis for the nifuroxazide mechanism of action in cancer. Graphical Abstract: Highlights: ALDH1 bio-activates nifuroxazide leading to ALDH1 inactivation and cytotoxicity Nifuroxazide selectively eradicates ALDH1 High melanoma tumor-initiating cells Targeted therapy increases ALDH1 in some patient melanomas and cell line models Targeting ALDH1 High cells with nifuroxazide is an orthogonal therapeutic strategy Abstract : A major challenge for cancer treatment is that tumors are comprised of subpopulations with differing growth potential and drug sensitivity. Here, Sarvi and colleagues reveal that the clinically approved antibiotic, nifuroxazide, selectively eliminates ALDH1 High melanoma-initiating cell subpopulations. This conceptual advance opens up new avenues in drug repurposing and melanoma therapy.